Adi Shankaracharya: hinduism`s greatest thinker - "Varma, Pavan K." (Chennai, 2018)
This book is a comprehensively-researched and detailed account of Adi Shankara's life and philosophy.. a valuable addition to the contemporary literature on Hinduism, a tribute to its scientific and philosophic basis, and an affirmation that it is much more than today's political ideologues depict.
Keywords: Hindu Philosophy